Genetic characterization of wild stocks of prawns macrobrachium rosenbergii using random polymorphic DNA markers. - See, Leng Min; Hassan, Rosli; Tan, S.G.; Bhassu, Subha (Asian Network for Scientific Information (ANSINET), 2008)
Random amplified polymorphic DNA was used to study the genetic diversity and assay polymorphisms among eleven populations of Macrobrachium rosenbergii in Malaysia. The RAPD procedure generated 205 markers in the 11 populations. and a large level of polymorphisms was observed in all populations. The unweighted pair group method with arithmetic averaging (UPGMA) clustering procedure based on the markers identified three major clusters among all populations. The results of the present study showed that RAPD based fingerprinting were a useful tool to assess the genetic variability of freshwater prawn, M. rosenbergii. Assessing high genetic variability within and among M. rosenbergii is considered important genetic resources as it has direct benefit for conserving wild stocks, greater potential for improvement and serves as invaluable resource for different selection criteria, especially when planning breeding or crossbreeding programs.